2011
DOI: 10.1002/ijc.26410
|View full text |Cite
|
Sign up to set email alerts
|

Tumor lactic acidosis suppresses CTL function by inhibition of p38 and JNK/c‐Jun activation

Abstract: Lactic acidosis is common to most solid tumors and has been found to affect infiltrating immune cells. Here we document effector phase inhibition of cytotoxic T cells (CTLs) involving complete blockage of cytokine production and partial impairment of lytic granule exocytosis. Lactic acidosis impaired TCR‐triggered phosphorylation of JNK, c‐Jun and p38, while not affecting MEK1 and ERK. The select targeting of signaling proteins involved in IFNγ production (JNK/c‐Jun, p38) without affecting those jointly used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
195
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(201 citation statements)
references
References 28 publications
5
195
0
1
Order By: Relevance
“…Among the natural ligands of PPAR, various eicosanoids, such as leucotriene B4, are generated during inflammatory responses [20,21]. In addition to these effects of ligand-bound PPAR on NF-B and c-jun, it has also been reported that ligand-free PPAR may inhibit the phosphorylation of p38 [22], a kinase that also promotes IFN transcription downstream of TCR stimulation [23]. Thus, we analyzed the in vitro response of human V9V2 T cells stimulated with a PPAR agonist, LY171883.…”
Section: Resultsmentioning
confidence: 99%
“…Among the natural ligands of PPAR, various eicosanoids, such as leucotriene B4, are generated during inflammatory responses [20,21]. In addition to these effects of ligand-bound PPAR on NF-B and c-jun, it has also been reported that ligand-free PPAR may inhibit the phosphorylation of p38 [22], a kinase that also promotes IFN transcription downstream of TCR stimulation [23]. Thus, we analyzed the in vitro response of human V9V2 T cells stimulated with a PPAR agonist, LY171883.…”
Section: Resultsmentioning
confidence: 99%
“…The increased production of lactate has been correlated to increased metastatic potential (24)(25)(26). In terms of lactate's impact on immune cells, recent studies have shown that lactate suppresses the function of tumor-specific T cells, inhibits tumor specific cytotoxic T cell activity (27), and induces defect in signal transduction (28). Lactate/low pH also alters the Ag-presenting ability of dendritic cells (29), inhibits cytotoxic activity (30), and promotes IL-23/IL-17 proinflammatory pathway (31).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the inflammatory response is often necessary for tumor progression, and elevated numbers of inflammatory cells, such as tumor-associated macrophages, connote poor prognosis (41). Furthermore, lactate in the tumor cell milieu impairs the adaptive immune response, disabling immune surveillance (43)(44)(45)(46). Thus, lactate also appears to promote tumorigenesis via non-tumor cell-mediated effects on the inflammatory and immune responses.…”
Section: Figurementioning
confidence: 99%